2005
DOI: 10.1097/01.ccm.0000157788.20591.23
|View full text |Cite
|
Sign up to set email alerts
|

Increasing mean arterial pressure in patients with septic shock: Effects on oxygen variables and renal function*

Abstract: Increasing mean arterial pressure from 65 to 85 mm Hg with norepinephrine neither affects metabolic variables nor improves renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
139
3
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(167 citation statements)
references
References 33 publications
14
139
3
8
Order By: Relevance
“…In fact, there is no evidence that higher values of blood pressure are of benefit in septic patients. This conclusion is supported by some recently published clinical studies, which have not shown improvement in renal function, splanchnic perfusion or oxygen variables when mean arterial pressure was increased with noradrenalin from 65 to 85 mmHg in volume-resuscitated patients [27,28].…”
Section: Discussionsupporting
confidence: 73%
“…In fact, there is no evidence that higher values of blood pressure are of benefit in septic patients. This conclusion is supported by some recently published clinical studies, which have not shown improvement in renal function, splanchnic perfusion or oxygen variables when mean arterial pressure was increased with noradrenalin from 65 to 85 mmHg in volume-resuscitated patients [27,28].…”
Section: Discussionsupporting
confidence: 73%
“…In a single-center trial [26], dose titration of norepinephrine from 65 to 75 and 85 mm Hg raised cardiac index (from 4.7 ± 0.5 to 5.5 ± 0.6 L/min/m 2 ) but did not change urinary flow, arterial lactate levels, oxygen delivery and consumption, gastric mucosal Pco 2 , RBC velocity, or skin capillary flow. Another single-center [27] trial compared, in norepinephrine-treated septic shock, dose titration to maintain MAP at 65 mm Hg versus achieving 85 mm Hg. In this trial, targeting high MAP increased cardiac index from 4.8 (3.8-6.0) to 5.8 (4.3-6.9) L/min/m 2 but did not change renal function, arterial lactate levels, or oxygen consumption.…”
mentioning
confidence: 99%
“…Because a MAP level of 65 mmHg is a survival factor in critically ill patients [88], especially during sepsis [89][90][91], this value is usually considered as the lowest acceptable level required for maintaining renal perfusion during AKI [92]. A diastolic arterial pressure <50-55 mmHg is associated with an increased AKI occurrence during septic shock [93,94]. Because the threshold for renal autoregulation may be higher in the elderly and patients with a cardiovascular history, the requirement of maintaining MAP above a 65-mmHg threshold is frequently questioned for these patients.…”
Section: (Grade 2+) Strong Agreementmentioning
confidence: 99%